2000
DOI: 10.1007/s003440000005
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Tissue Stress Affects the Orientation of Cortical Microtubules in the Epidermis of Sunflower Hypocotyl

Abstract: In turgid multicellular organs, it is convenient to differentiate between the two kinds of tensile forces acting in cell walls as a result of turgor pressure. The primary forces occur both in situ and in cells isolated from the organ, whereas the secondary forces occur only in situ. The latter are an unavoidable physical consequence of the variation in mechanical parameters of tissues forming layers or strands. The most rigid tissue is under maximal tensile force, whereas the least rigid is under maximal compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
87
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(93 citation statements)
references
References 32 publications
5
87
0
1
Order By: Relevance
“…Moreover, in sunflower, the epidermis is vital in the hypocotyl growth control. 46 In Phaseolus vulgaris, it is epidermal cells that display partially reversible changes in the length of the bending, mobile part of the shoot. 44 The endodermal cells (statocytes with amyloplasts functioning as statoliths) also play an important role in circumnutations, as revealed by scr mutants of Arabidopsis and Pharbitis nil.…”
Section: Cellular and Molecular Basis For Circumnutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in sunflower, the epidermis is vital in the hypocotyl growth control. 46 In Phaseolus vulgaris, it is epidermal cells that display partially reversible changes in the length of the bending, mobile part of the shoot. 44 The endodermal cells (statocytes with amyloplasts functioning as statoliths) also play an important role in circumnutations, as revealed by scr mutants of Arabidopsis and Pharbitis nil.…”
Section: Cellular and Molecular Basis For Circumnutationsmentioning
confidence: 99%
“…53,54 Epidermal cells as well as parenchymal-subepidermal cells are involved in generation of circumnutations. 22,46 Therefore, epidermal and parenchymal cells might function as motor cells. Figure 5 presents a scheme of a hypothetical cell, i.e., a part of the stem motor tissue, with marked elements constituting the oscillator and elements involved in circumnutations.…”
Section: Hypothetical Electrophysiological Model Of Circumnutationsmentioning
confidence: 99%
“…Many external factors, like plant growth regulators (see review by Shibaoka, 1994), electric field (Hush and Overall 1991;Blackman and Overall 1995), mechanical stresses Schopfer 1997, 1998;Hejnowicz et al 2000), and developmental factors (Liang et al 1996;Granger and Cyr 2001) affect the cMT orientation with respect to cell axis. The same is true also for light (Laskowski 1990;Nick et al 1990;Zandomeni and Schopfer 1993;Ueda and Matsuyama 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The last significant scientific contribution pointed out by Zygmunt himself were his works with the late Andreas Sievers, devoted to tissue stresses. [16][17][18] They explained the existence of structural tissue stresses that are the indirect result of the turgor pressure. These stresses exist in "green" plant organs composed of turgid tissues that differ in cell size and thickness, and mechanical properties of the cell walls.…”
mentioning
confidence: 99%
“…Together with Lewis J. Feldman, Zygmunt showed the role that mechanical forces generated by microtubules at kinetochores play in chromosome segregation during Oenothera meiosis. 33 In other papers, Zygmunt with colleagues from his Department at the University of Silesia, showed that, in sunflower hypocotyl epidermis, cortical microtubules orientation is related to mechanical stress (it is noteworthy that one of these papers 18 appeared in the volume of Journal of Plant Growth Regulation devoted to memory of Zygmunt's friend -Paul B. Green).…”
mentioning
confidence: 99%